Investigating healthcare IT innovations: a "conceptual blending" approach. Issue 7 (16th November 2015) - Cranfield, Steven; Hendy, Jane; Reeves, Barnaby; Hutchings, Andrew; Collin, Simon; Fulop, Naomi
Abstract : Purpose: – The purpose of this paper is to better understand how and why adoption and implementation of healthcare IT innovations occur. The authors examine two IT applications, computerised physician order entry (CPOE) and picture archiving and communication systems (PACS) at the meso and micro levels, within the context of the National Programme for IT in the English National Health Service (NHS). Design/methodology/approach: – To analyse these multi-level dynamics, the authors blend Rogers' diffusion of innovations theory (DoIT) with Webster's sociological critique of technological innovation in medicine and healthcare systems to illuminate a wider range of interacting factors. Qualitative data collected between 2004 and 2006 uses semi-structured, in-depth interviews with 72 stakeholders across four English NHS hospital trusts. Findings: – Overall, PACS was more successfully implemented (fully or partially in three out of four trusts) than CPOE (implemented in one trust only). Factors such as perceived benefit to users and attributes of the application – in particular speed, ease of use, reliability and flexibility and levels of readiness – were highly relevant but their influence was modulated through interaction with complex structural and relational issues. Practical implications: – Results reveal that combining contextual system level theories with DoIT increases understanding of real-life processes underpinning implementation of IT innovations within healthcare. They also highlight important drivers affecting success of implementation, including socio-political factors, the social body of practice and degree of "co-construction" between designers and end-users. Originality/value: – The originality of the study partly rests on its methodological innovativeness and its value on critical insights afforded into understanding complex IT implementation programmes.